Surgery Versus ATMPs: An Example From Ophthalmology - Magrelli, Federica M.; Merra, Alessia; Pellegrini, Graziella (Frontiers in Bioengineering and Biotechnology, 2020)
Advanced therapy medicinal products (ATMPs) are the new frontier of medicine. ATMPs are set out to satisfy unmet medical needs and provide new innovative, cutting-edge therapies for serious or life-threatening diseases, thus providing new therapeutic options for people with few or no possibility of treatment. They are divided into four groups including gene therapy medicinal products (GTMPs), cell-based therapy medicinal products (CTMPs), tissue-engineered products (TEPs), and combined ATMPs, which in Europe refer to products that incorporate one or more medical devices with any of the previously mentioned ATMPs as part of the advanced medicine product [1] [2]. ATMPs can potentially have long-term benefits, thus bringing a long-lasting positive impact on patient health. ATMP therapies are often administered just once or twice, which gives patients the possibility to heal quickly compared to traditional therapies. They also provide a long-term saving opportunity, both in terms of costs of treatments and procedures that are no longer necessary and in terms of quality of life and productivity. The resolution of the patient’s illness has a monetary impact on the patient, the patient’s caretakers, and especially on the society [3]. The aim of this paper was to provide an overview on the use of ATMPs approved in Europe, with a focus on blindness and visual impairment and the related economic burden. In this case study, the effective cost of a blind patient in different European countries was compared after treatment with ATMPs or traditional therapies, focusing on visual impairment caused by corneal opacity. Our evaluation includes an overview of the global economic impact of the two types of therapies on the society. We estimated direct healthcare costs, direct non-healthcare costs, and labour productivity losses, to include costs on healthcare, services, patients, their families and for the society in general and we could conclude that the costs of the two therapeutic approaches are comparable.